Attitudes of Parents towards Children with Specific Learning Disabilities - Mysore Narasimha Vranda; Indiramma Venkatakrishnashastry; Dr. Chandramuki (Disability, CBR and Inclusive Development)
Purpose: This study explored parental attitudes towards children with specific learning disabilities. Method: The study sample comprised parents of 60 children (30 boys and30 girls) with Specific Learning Disability (SLD) who attend the Child and Adolescent Psychiatry Out-Patient Department at National Institute of Mental Health and Neurosciences, Bangalore, India. The attitudes of parents were assessed using the Parental Attitude Scale. Results: The results revealed significant differences related to gender of the children on various domains of the scale. Conclusion: The study highlights the need to educate parents to lower their expectations for children with specific learning disabilities, and to strengthen the social support network of these children’s families.